THE APPLICATION OF SOCIAL AND ENVIRONMENTAL CARE CHARACTER EDUCATION THROUGH LEARNING OF SOCIAL EDUCATION IN ELEMENTARY SCHOOL OF NANGGUNG DISTRICT - R, M Dahlan; Priatna, De Ajeng Ayu; Yono, Yono (Institut Keguruan dan Ilmu Pendidikan Siliwangi, 2021)
This research was conducted to describe the application of social and environmental care character education in social science learning in elementary schools. This study uses qualitative methods with data collection techniques in the form of interviews, observations, and documentation. The primary data in this study were fourth-grade teachers at the Nanggung District Elementary School. Based on the results of the research conducted, data obtained that there is an application of social and environmental care character education that is integrated into Social Science learning. the application of social and environmental care character education in addition to social studies learning is assisted through school programs that serve as supporters in the formation of social and environmental caring characters. The impact of implementing social and environmental care character education that is integrated into social studies subjects students are accustomed to loving environmental cleanliness by disposing of garbage in its place, being able to maintain environmental integrity by maintaining plants around schools, preserving the environment by planting trees around empty places and having sensitivity to give and help people in need by sharing each other in the form of support and materials and visiting sick friends.